DIGITAL MARKETING OF UNSTABLE TOURIST DESTINATIONS How Do National Tourism Organizations Communicate Via Website? Case Greece and case Egypt. - Leivo, Aleksi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
The past few years have been difficult for several countries in southern Europe and in the Middle East. Certain popular tourist destinations have confronted challenging times, which have had, inter alia, a negative impact on international tourist arrivals. Yet, globally, the travel and tourism sector has been growing steadily for years now. While some countries have been in distress, the whole macro environment has gone forward and the competition between nations has become fiercer than ever before, making nation branding a strategic instrument, not solely for attracting tourist, but also for attracting investments, exports and labor. The main purpose of the study was to find out how national tourism organizations, particularly the ones of Greece and Egypt would communicate online despite the unstable times they had been facing, and especially how they would deal with challenging and unpleasant matters in terms of rhetoric and communication. The answers were provided with the help of qualitative content analysis. The researcher did go through the official tourism websites of the two selected case countries and did analyze their content such as communication in the form of texts, images, symbols and videos. Only the English language versions of the sites were under inspection. The gathering of the data from the websites www.visitgreece.gr (Visit Greece | The Official website of the Greek Tourism Organisation) occurred between 17.9-7.12.2016 and 4.1.2017-30.3.2017 for www.egypt.travel (Egyptian Tourism Authority). In order to ease the analyzing process and to produce an effortlessly approachable and decent looking study, parts of both websites were captured with the help of Snipping Tool. Likewise, a 27 inch Asus monitor with a resolution of 2560 x 1440 pixels and the web browser Mozilla Firefox 49.0.2 were utilized for conducting the analysis. It was particularly interesting to become aware of how these national tourism organizations were reacting to these unfavorable circumstances they were facing for a rather long period of time. Fundamentally, in terms of information and message, the two websites were very similar. Overall, it could be said that the national tourism organizations under inspection did seem to communicate online essentially like any other commercial, private or governmental actor. And that, negative and potentially harmful matters were indecently left out at the detriment of transparency and honesty.